Forensic Entomology: A Comprehensive Review - Sundus Mona; Muhammad Jawad; Saadia Noreen; Saqib Ali; Allah Rakha (Advancements in Life Sciences, 2019)
Determination of post mortem interval is done with various methods depending upon the condition of the dead body and the circumstances in which it is found. Ruling out foul play in unnatural deaths has been an enigma of a sort for forensic pathologists and scientists all over the world. The methods to determine the cause and manner of death keep on emerging with ongoing researches in the fields of forensic sciences. Many methods have been devised to determine cause, manner and specifically time since death. Forensic entomology is one such field that aids in determination of time since death, especially in putrefied corpses found in different habitats in mysterious unknown circumstances. The field keeps on emerging with the advent of new techniques on molecular level, including DNA analysis and identification based on entomological data that has diversified over the years. The standards and guidelines for entomological data collection and processing needed for implication on the crime scene must be revised now and again for assistance of crime scene investigators, scientists, entomologists and pathologists. Various factors must be considered while processing entomological data that affect post mortem intervals. The keen study of life cycles, groups of similar insects, valid and standard methods of insect collection, breeding and identification can give a lead on cause, manner, time, place and circumstances of unknown or unnatural deaths.